Dynamic Analysis of a Quadcopter Using PID, Adaptive and LQR Control Methods - Altınors, Ayhan; Kuzu, Funda (My University, 2021)
In this study, different control methods for controlling the position and angle values for the quadcopter (UAV) that take off and land vertically are simulated with MATLAB/Simulink. First of all, a mathematical model was created with the Newton-Euler method, taking into account the dynamics of the quadcopter system. The focus of the study is to investigate the appropriate control method for the position control of the quadcopter. For the linear model of the quadcopter system, PID, LQR and Adaptive Control methods, and for the nonlinear model of the quadcopter system. PD Control simulation has been done. The mentioned control methods have been applied to the system and the control of the movement of the system in each axis has been examined. The obtained results are compared with each other to see the performance of the controllers and the most appropriate control method for the quadcopter was determined with comparisons and tracking scenarios.
Keywords: Adaptive; LQR